The use of willingness to pay experiments : estimating demand for piped water connections in Sri Lanka - Van Houtven, George L. (Policy research working paper, 2006)
"The authors show how willingness to pay surveys can be used to gauge household demand for improved network water and sanitation services. They do this by presenting a case-study from Sri Lanka, where they surveyed approximately 1,800 households in 2003. Using multivariate regression, they show that a complex combination of factors drives demand for service improvements. While poverty and costs are found to be key determinants of demand, the authors also find that location, self-provision, and perceptions matter as well, and that subsets of these factors matter differently for subsamples of the population. To evaluate the policy implications of the demand analysis, they use the model to estimate uptake rates of improved service under various scenarios-demand in subgroups, the institutional decision to rely on private sector provision, and various financial incentives targeted to the poor. The simulations show that in this particular environment in Sri Lanka, demand for piped water services is low, and that it is unlikely that under the present circumstances the goal of nearly universal piped water coverage is going to be achieved. Policy instruments, such as subsidization of connection fees, could be used to increase demand for piped water, but it is unclear whether the benefits of the use of such policies would outweigh the costs. "--World Bank web site